Wie het mooist valt : roman - Nović, Sara, 1987-; Bijnsdorp, Maaike; Schaap, Lucie (Amsterdam : Meulenhoff, 2017)
Het zorgeloze leven van een jong meisje wordt verstoord door de Joegoslavische burgeroorlog.